Adult Developmental Experiences of African American Doctoral Student Mothers: Illuminating Generativity Processes. Issue 2 (7th October 2018) - Appling, Brandee; Haskins, Natoya Hill; Daigle, Jolie
Abstract : This phenomenological study examined the developmental experiences of 8 African American doctoral student mothers. Findings and related themes indicate that identity and curriculum preparation influence African American doctoral student mothers' adult development. Implications for training and practice are included along with recommendations for future research.